2023
DOI: 10.3389/fvets.2023.1240227
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of brix refractometry for estimating bovine colostrum immunoglobulin G concentration

Donald Sockett,
Ryan M. Breuer,
Lindsey W. Smith
et al.

Abstract: Many dairy operations uses a Brix refractometer to assess the quality of first-milking colostrum. This study investigated whether a digital Brix refractometer could be used in a model to predict colostrum IgG concentration and whether more than one %Brix threshold could be used for different colostrum IgG concentrations. Colostrum from 182 animals was tested using a digital Brix refractometer and by single radial immunodiffusion. Statistical analysis, using simple linear regression to relate %Brix results with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The calf care providers for this case followed on-farm protocols for colostrum feeding that are based on current best practice recommendations for the industry (1,20). Previous publications have suggested that feeding a smaller volume of colostrum is preferable because there is a higher efficiency of absorption of bovine immunoglobulin (21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The calf care providers for this case followed on-farm protocols for colostrum feeding that are based on current best practice recommendations for the industry (1,20). Previous publications have suggested that feeding a smaller volume of colostrum is preferable because there is a higher efficiency of absorption of bovine immunoglobulin (21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, force-feeding colostrum using an esophageal tube feeder can be controversial and, in some countries, tube feeding is prohibited except for medical reasons (28). Abdominal distension and colic caused by large-volume colostrum feeding can be mitigated by gaining further knowledge of how to appropriately assess colostrum quality (20). Additionally, calf care providers can be trained on the appropriate administration of colostrum, which includes identification of the risks and complications of overfeeding with an esophageal tube feeder (7)(8)(9)20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-two multisource, crossbreed, multiparous beef cows [ 20 ] and first-calf heifers [ 12 ] were enrolled in this study from February 2017 through March 2018. Cows and heifers were synchronized with a modified 7-d CIDR-synch protocol and artificially inseminated (AI) as previously described [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recommendations for colostrum replacement in dairy calves call for the administration of a high volume (~4 L) of high-quality (>22% Brix) maternal colostrum or colostrum replacer powder (300 g of IgG) within the first 2–4 h of birth [ 16 , 17 ]. These recommendations may be impractical for beef calves for several reasons, including lack of complete separation of the dam, excessive volume in relation to calf body weight, potential disruption of nursing behavior due to gastrointestinal distention, and colic [ 18 , 19 , 20 ]. The overarching goal of colostrum supplementation and/or replacement in beef calves should be to minimize the negative impact of FTPI and ITPI while avoiding disruption of normal nursing behavior [ 18 , 21 ].…”
Section: Introductionmentioning
confidence: 99%